Stroke Prevention Behaviors In Elderly Patients - Widiastuti; Rezi Septi Repa, Alfa; Puspita Sari, Ade; Anita, Irma; Aisah, Nur; Rustandi, Handi (Universitas Dehasen Bengkulu, 2025)
High blood pressure or what can be interpreted as hypertension is a health problem that can affect anyone, both young and old. Hypertension is one of the most deadly health problems on the global stage. Hypertension or high blood pressure is a significant medical condition which can specifically cause risks to the heart, brain, kidneys and other health problems (Musa, 2022) Hypertension is one of the causes of stroke because hypertension can damage blood vessels and increase the risk of stroke, heart attack and kidney failure. In the elderly, hypertension is more difficult to control and can increase the risk of complications. Stroke is an event that occurs when blood flow to the brain is cut off. In the elderly, strokes occur more often and can cause disability and death. It can be concluded that age, mobility, activity, obesity and hypertension are interrelated factors that can increase the risk of stroke in the elderly (Anshari, 2020). The level of education affects a person, how he or she absorbs information and provides a basis for life. Formal education can also provide more value for individuals, especially in accepting new things. This may also be related to the level of education in Indonesia, where the majority of education is still middle to lower. One preventive effort to increase the level of client knowledge regarding the dangers of a disease is by providing health education. Health education is an independent nursing intervention to help clients overcome their health problems through learning activities, thereby increasing knowledge and behavior to prevent disease and improve health (Hapitria & Padmawati, 2021).